Histochemical and biochemical analysis of the size-dependent nanoimmunoresponse in mouse Peyer's patches using fluorescent organosilica particles - Awaad A (Dove Medical Press, 2012)
Aziz Awaad1,2, Michihiro Nakamura1, Kazunori Ishimura11Department of Anatomy and Cell Biology, the University of Tokushima Graduate School, Kuramoto, Tokushima, Japan; 2Department of Zoology, Faculty of Science, Sohag University, Sohag, EgyptBackground/objective: The size-dependent mucosal immunoresponse against nanomaterials (nanoimmunoresponse) is an important approach for mucosal vaccination. In the present work, the size-dependent nanoimmunoresponse of mouse Peyer's patches (PPs) and immunoglobulin A (IgA) level was investigated using fluorescent thiol-organosilica particles.Methods: Various sizes of fluorescent thiol-organosilica particles (100, 180, 365, 745, and 925 nm in diameter) were administered orally. PPs were analyzed histochemically, and IgA levels in PP homogenates, intestinal secretions around PPs, and bile were analyzed biochemically.Results: When compared with the larger particles (745 and 925 nm), oral administration of smaller thiol-organosilica particles (100, 180, and 365 nm) increased the number of CD11b+ macrophages and IgA+ cells in the subepithelial domes of the PPs. Additionally, administration of larger particles induced the expression of alpha-L-fucose and mucosal IgA on the surface of M cells in the follicle-associated epithelia of PPs and increased the number of 33D1+ dendritic cells in the subepithelial domes of the PPs. IgA contents in the bile and PP homogenates were high after the administration of the 100 nm particles, but IgA levels in the intestinal secretions were high after the administration of the 925 nm particles. Two size-dependent routes of IgA secretions into the intestinal lumen, the enterohepatic route for smaller particles and the mucosal route for larger particles were proposed.Conclusion: Thiol-organosilica particles demonstrated size-dependent nanoimmunoresponse after oral administration. The size of the particles may control the mucosal immunity in PPs and were useful in mucosal vaccination approaches.Keywords: thiol-organosilica particles, Peyer's patches immune cells, IgA, mucosal vaccination